Calcined ZnAl- and Fe3O4/ZnAl–layered double hydroxides for efficient removal of Cr(vi) from aqueous solution. Issue 117 (9th November 2015) - Yan, Liang-guo; Yang, Kun; Shan, Ran-ran; Yu, Hai-qin; Du, Bin
Abstract : Calcined ZnAl- and Fe3 O4 /ZnAl–layered double hydroxides (ZnAl–CLDH and Fe3 O4 /ZnAl–CLDH) were used as adsorbents to evaluate the uptake properties for Cr(vi ) removal from aqueous solution by batch equilibrium experiments. Abstract : Calcined ZnAl- and Fe3 O4 /ZnAl–layered double hydroxides (ZnAl–CLDH and Fe3 O4 /ZnAl–CLDH) were used as adsorbents to evaluate the uptake properties for Cr(vi ) removal from aqueous solution by batch equilibrium experiments. The XRD, FTIR and TEM results showed that the calcined ZnAl–LDH and Fe3 O4 /ZnAl–LDH recovered layered structures according to the memory effect of hydrotalcite. Optimized conditions of Cr(vi ) adsorption were obtained: 2.0 g L −1 adsorbent, initial solution pH of 3.0 and contact time of 60 min. The kinetic data was described better by a pseudo-second-order kinetic equation. The adsorption isotherms had a good fit with Langmuir and Freundlich models. Thermodynamic analyses indicated that the adsorption process was endothermic and spontaneous in nature. The adsorption mechanisms involved the reconstruction of LDHs, surface complexation, anion exchange and physical adsorption. The higher adsorption capacities of the calcined products suggested that the ZnAl–CLDH and Fe3 O4 /ZnAl–CLDH were potential adsorbents for Cr(vi ) removal from water and wastewater. Moreover, the magnetic Fe3 O4 /ZnAl–CLDH can be easily separated using a magnet after the adsorption process.